2013
DOI: 10.1021/ie4015974
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Kinetics of Foreign-Ion-Promoted Ilmenite Using Carbon Monoxide (CO) for Chemical Looping Combustion

Abstract: In a previous work by our group, a new kind of ilmenite oxygen carrier, namely, natural ilmenite particles impregnated with foreign ions (K+, Na+, or Ca2+), was reported as having a promoted reactivity. The objective of this work was to investigate the detailed reduction kinetics of the new foreign-ion-promoted ilmenite carrier. Ilmenite particles impregnated with different types of foreign ions, including K+, Na+, and Ca2+, at different loading ratios were investigated by thermogravimetric analysis (TGA) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…To study the impact of oxygen concentration on reaction rates, the O2 concentration was selected between 0-9 vol % for reduction and 1.5-21 vol % for oxidation. The reaction rate is presented in Equation (36): , (36) where Co2 is the O2 concentration at each time and Co2,eq is the O2 concentration at equilibrium. Equations 35 and 36 are also valid for oxidation reactions.…”
Section: Kinetic Studies Of Oxygen Carriers and Solid Fuels Using Tgamentioning
confidence: 99%
See 1 more Smart Citation
“…To study the impact of oxygen concentration on reaction rates, the O2 concentration was selected between 0-9 vol % for reduction and 1.5-21 vol % for oxidation. The reaction rate is presented in Equation (36): , (36) where Co2 is the O2 concentration at each time and Co2,eq is the O2 concentration at equilibrium. Equations 35 and 36 are also valid for oxidation reactions.…”
Section: Kinetic Studies Of Oxygen Carriers and Solid Fuels Using Tgamentioning
confidence: 99%
“…In general, natural minerals usually have lower reactivity than synthetic oxygen carriers. Research on improving natural mineral reactivity with the addition of metal oxides or alkali and alkaline metals (K+, Na+, or Ca+) has been reported [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Those compounds act as catalysts which can not only enhance pyrolysis and gasification [32], but also promote the reactivity of hematite. Bao et al found that the addition of foreign ions (K + , Na + or Ca 2+ ) could significantly promote the reduction rate of ilmenite [21,22]. Additionally, the consumption of CO and H 2 , which has an inhibiting effect on steam gasification, can increase the fuel conversion rate [33].…”
Section: Comparison Of Clc Performance Between Sewage Sludge and Coalmentioning
confidence: 99%
“…Besides, Ksepko [19] reports that sludge ash can be effectively used as a low-cost, valuable oxygen carrier in CLC process. In addition, it should be mentioned that a large amount of Ca is presented in sludge ash [20], which has been shown to be an efficient additive in oxygen carrier to promote the reactivity of carrier and catalyze gasification process [21,22]. Thus, the interaction between sludge ash and oxygen carrier cannot be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium oxide has well known interactions with iron oxide and the thermodynamics of the Ca-Fe-O system are available in the literature. CaO is cheap and more recent work by Bao et al [10] has shown that addition of foreign ions such as Ca 2+ , Na + and K + enhanced the reactivity of Ilemenite (an iron based mineral -FeTiO3) in looping reactions. Since CaO is often used as a fluxing agent in steel making, it might be expected that it's addition to the iron oxide might worsen sintering.…”
Section: Introductionmentioning
confidence: 99%